On the term structure of futures and forward prices - Tomas Björk; Camilla Landén (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
We investigate the term structure of forward and futures prices for models where the price processes are allowed to be driven by a general marked point process as well as by a multidimensional Wiener process. Within an infinite dimensional HJM-type model for futures and forwards we study the properties of futures and forward convenience yield rates. For finite dimensional factor models, we develop a theory of affine term structures, which is shown to include almost all previously known models. We also derive two general pricing formulas for futures options. Finally we present an easily applicable sufficient condition for the possibility of fitting a finite dimensional futures price model to an arbitrary initial futures price curve, by introducing a time dependent function in the drift term.
Keywords: E43; G13; 330; term structure; futures price; forward price; options; jump-diffusion model; affine term structure